LOYALTY MANAGEMENT driving engagement with loyalty programs and customer experiences. - Ziliani, Cristina; Ieva, Marco (Research fellow in marketing) (ROUTLEDGE, 2025)
In this insightful text, Cristina Ziliani and Marco Ieva trace the evolution of thinking, contemporary themes and practice in loyalty management. Loyalty management is increasingly identified with the design and management of a quality customer experience in the journey across the many touchpoints that connect the customer with the brand. Evaluating the research on best practice and offering concrete examples from industry, including seven international case studies, the authors present a fresh take on the tools, strategies and skills - from loyalty programs to CRM to CX - that underpin loyalty's key significance in marketing. New to this 2nd edition, readers will find: A new chapter exploring the strategic relevance of loyalty management for company long-term profitability. A new chapter on loyalty and sustainability, based on research on 90 case studies of loyalty initiatives worldwide, supporting organizations as they strive to meet their ESG requirements and demonstrating how they can use their loyalty programs to do so. Coverage of the role of touchpoints in developing loyalty, from physical stores to voice assistants, drawing from state-of-the-art international scientific research. Discussion of metrics and KPIs for measuring loyalty management, as well as further exploration of the role of emerging technologies, in particular the application of predictive and generative artificial intelligence to loyalty strategies. New case studies and examples from a broader range of industries and geographical regions. Celebrating 25 years of experience in research, consulting and teaching within the Osservatorio Fedelt UniPR (Loyalty Observatory), the authors have compiled a unique research-based, practice-oriented text. It will guide marketers, business leaders and postgraduate students through the changes in marketing thought and practice of loyalty management - including omnichannel, AI and sustainability - as well as offering practical guidance on the skills and capabilities that companies need if they want to be successful at delivering essential, loyalty-driving customer experiences.
Keywords: Customer loyalty.; Customer relations.; elektronické knihy; electronic books